2007
DOI: 10.1002/lt.21083
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study comparing ligation with propranolol for primary prophylaxis of variceal bleeding in candidates for liver transplantation

Abstract: Whether beta-blockers (BB) or banding is the best therapy for primary prophylaxis of variceal bleeding is subject to debate. A randomized comparison between the 2 treatments was performed in candidates for liver transplantation (LT). A total of 62 patients with Child-Turcotte-Pugh B-C cirrhosis and high risk varices received propranolol (31) or variceal banding (31). The primary endpoint was variceal bleeding. There were 2 variceal hemorrhages (6.5%) in the banding group, related to postbanding ulcers, and 3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 24 publications
3
52
0
3
Order By: Relevance
“…Our experience is consistent with that of Norberto et al, 1 who found that prophylactic variceal ligation led to clinically significant iatrogenic bleeding. We have since streamlined our policy and have stopped performing prophylactic variceal ligation in patients awaiting LDLT.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Our experience is consistent with that of Norberto et al, 1 who found that prophylactic variceal ligation led to clinically significant iatrogenic bleeding. We have since streamlined our policy and have stopped performing prophylactic variceal ligation in patients awaiting LDLT.…”
supporting
confidence: 92%
“…We read the articles by Norberto et al 1 and Boyer 2 with interest. As the authors have highlighted, various randomized controlled studies and meta-analysis have consistently showed that although endoscopic variceal ligation is better at preventing first variceal bleed than beta blockers, it is also associated with adverse effects and, in particular, fatal adverse effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Their experience is consistent with ours and different from that reported by Jutabha et al 3 In all 3 studies, the patients were liver transplant candidates and thus constituted a particular subgroup of patients with cirrhosis, as underlined also by Boyer. 4 In our opinion, this favors the use of beta-blockers instead of banding for primary prophylaxis for at least 2 reasons.…”
supporting
confidence: 86%
“…Krwawienia z owrzodzeń po opaskowaniu obserwowano u 6,5-7% pacjentów, w tym jeden pacjent zmarł. Wystąpiły one 9 i 11 dni po pierwszej eradykacji [206]. Szepke i wsp.…”
Section: Transplantacja Wątrobyunclassified